"Insecticide Resistance /Susceptibility Monitoring in Anopheles pulcherrimus (Diptera: Culicidae) in Ghasreghand District, Sistan and Baluchistan Province, Iran" - AH Zahirnia; H Vatandoost; M Nateghpour; E Djavadian (Tehran University of Medical Sciences, 2002)
Two organochlorine, one organophosphate, two carbamate and two pyrethroid insecticides have been studied for their comparative study against fieldcollected An.pulcherrimus. The trail was conducted in Ghasreghand district, Sistan and Baluchistan province, Southeastern Iran using WHO impregnated papers at the diagnostic dose. Results revealed that this species exhibit resistant to 0.4% dieldrin (mortality 86 ± 2.07). Dose response regression line from interval exposure times to 0.4% dieldrin showed that LT50 and LT90 was 14 and 76 minutes, respectively. The efficacles of other insecticides such as 4% DDT, 5% malathion, 0.1% bendiocarb, 0.1% propoxur, 0.25% permethrin and 0.1% lambdacyhalothrin were maximum when mosquitoes exposed 1 hour at diagnostic dose followed by 24 hour recovery period.